Use of Modular and Wearable Technical Means of Disinfection During Liquidation of Emergency Situations - A. S. Morozov; V. P. Lakomov; A. A. Noskov (Вестник войск РХБ защиты, 2023)
In the process of liquidation of emergency situations of biological nature (ESBN) by the NBC Protection Corps of the Armed Forces of the Russian Federation, the modern modular and wearable technical means of disinfection based on an aerosol method of treatment of objects were widely used. The purpose of the work is to summarize experience of the use of modular and wearable technical means of disinfection during the liquidation of biological emergency. The most intensive use of mobile technical means of disinfection was carried out for more than two years in Chkalovsky airfield by the combined NBC protection group, which carried out work on the disinfection of aircraft of the Military Space Forces and the cargo transported by them against the pathogen of coronavirus infection. The main volume of work on disinfection of cargo compartments and cockpits of pilots of aircraft as well as cargo was performed in the aerosol method with the use of the following technical means: CDA (Aerosol Disinfection Complex) complex, the bagpack motorized and manual sprayers. The aerosol treatment method and the formulation based on ethyl alcohol provided high productivity of works, low manual labor costs, and reliable disinfection of objects with low consumption of preparation. Thus, the processing time of the cargo compartment of AN-124 aircraft with the help of autonomous modules of the CDA or backpack sprayers STIHL SR 450 did not exceed 20 minutes, and the consumption of the recipe was not more than 100 cm3 ×m2. The use of modern modular and wearable disinfection means in the NBC protection units will ensure the increase of efficiency of disinfection measures in the interests of troops and population of the Russian Federation.